Through-bolt push out effects on the behavior of hybrid masonry systems. (15th August 2015) - Nistor, Mihaela; Gao, Zhenjia; Stanciulescu, Ilinca
Highlights: Analyze through-bolt push-out effects on the hybrid masonry systems behavior. Establish and calibrate a computational framework to model hybrid masonry systems. Correlate the size of the nonlocal domain with the geometry of the system. Provide recommendations for reinforcement layout and location of connectors to maximize structural capacity. Abstract: This paper provides specifications necessary for designing hybrid masonry systems that resist through-bolt push out effects. Hybrid masonry is a relatively new structural system that can be used in seismic areas and comprises masonry panels connected to frames through steel plate connectors. However, masonry break-out at the connection between the steel plates and the masonry panel requires further analysis to better understand the load transfer mechanism of the hybrid masonry system. Therefore, we use a computational framework to model the hybrid masonry that uses a typical plasticity model with hardening for the steel components and a nonlocal two-scalar damage model that accounts for tension and compression for the masonry panel. Based on parametric studies conducted using this framework we provide recommendations for the through-bolt location and for the reinforcement percentage and location within the masonry panel to achieve best results in the load transfer mechanism of the hybrid masonry system during a seismic event.